2021
DOI: 10.1515/jisys-2021-0164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of several initialization methods on arithmetic optimization algorithm performance

Abstract: Arithmetic optimization algorithm (AOA) is one of the recently proposed population-based metaheuristic algorithms. The algorithmic design concept of the AOA is based on the distributive behavior of arithmetic operators, namely, multiplication (M), division (D), subtraction (S), and addition (A). Being a new metaheuristic algorithm, the need for a performance evaluation of AOA is significant to the global optimization research community and specifically to nature-inspired metaheuristic enthusiasts. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The basic particle swarm optimization algorithm can be used to optimize the system matrix and determine the optimal value in the process of continuously tracking the extreme value, which is easy to realize and has fast convergence speed. However, due to the single optimization method, the optimal solution often cannot break through its own limitations [17,18]. The hybrid particle swarm optimization algorithm proposed in this paper uses genetic algorithm for reference; that is, genetic algorithm is introduced into particle swarm optimization algorithm to make particles reach the optimal value in the cross mutation with individual extreme value and population extreme value, so as to solve the problem that particle similarity cannot jump out of the boundary of local optimal solution when the population converges.…”
Section: Periodic Message Scheduling Optimization Based Onmentioning
confidence: 99%
“…The basic particle swarm optimization algorithm can be used to optimize the system matrix and determine the optimal value in the process of continuously tracking the extreme value, which is easy to realize and has fast convergence speed. However, due to the single optimization method, the optimal solution often cannot break through its own limitations [17,18]. The hybrid particle swarm optimization algorithm proposed in this paper uses genetic algorithm for reference; that is, genetic algorithm is introduced into particle swarm optimization algorithm to make particles reach the optimal value in the cross mutation with individual extreme value and population extreme value, so as to solve the problem that particle similarity cannot jump out of the boundary of local optimal solution when the population converges.…”
Section: Periodic Message Scheduling Optimization Based Onmentioning
confidence: 99%
“…According to the literature, one type of adaptation strategy to include well-balanced exploration and exploitation in any NIOA is to vary the population size. Experiments had been performed under three conditions: large population and small number of iterations, small population and large number of iterations, and large population and large number of iterations [37]. The findings revealed that AOA is affected by the size of the population, and a large population is required for the best results.…”
Section: Parameter Sensitivitymentioning
confidence: 99%
“…The representation of a group of dwarf mongooses, which also represents the entire population, is modeled using Eq. (1). Since the population of the dwarf mongoose is often composed of the alpha groups, juvenile group, and scout (including babysitters), we derive the alpha group from the population to allow for allocating the remaining individuals in the population for the other two subgroups.…”
Section: The Dmo Modelmentioning
confidence: 99%
“…Optimization tries to find the best solution amongst a pool of other solutions. As such, optimization occurs naturally in many human endeavors and is deeply rooted in science, businesses, ecology, and manufacturing [ 1 ]. Basically, optimization is accomplished using either the mathematical or metaheuristic approach.…”
Section: Introductionmentioning
confidence: 99%